2015
DOI: 10.5539/ijef.v7n4p223
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Capital and Bank Risk: Evidence from Tunisia

Abstract: The capital and risk are two important variables in banking. Indeed , capital can protect banks against shocks and excessive risks. But according to other researchers , there is a positive relationship between capital and risk.In the context of this article, we looked at 18 banks in Tunisia over the period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), we found that there is a negative relationship between the capital and bank risk by applying a static panel method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…This result indicated the ineffective use of available assets to generate profit due to an increase in stringent capital requirements. All the models show that there is a negative relationship between bank size (SIZE) and profitability significant with NIP (at 10%), and ROA (at 1%) this result is supported by Moussa (2015) and Rizqi and Faisal (2017). Yousuf and Felföldi (2018) found that bank capital adequacy ratio in Syria affects profitability negatively as expressed by ROE they found that stricter capital requirements means better insurance for depositors, however, this leads to a decrease in the rate of return to shareholders.…”
Section: Regression Analysismentioning
confidence: 67%
See 1 more Smart Citation
“…This result indicated the ineffective use of available assets to generate profit due to an increase in stringent capital requirements. All the models show that there is a negative relationship between bank size (SIZE) and profitability significant with NIP (at 10%), and ROA (at 1%) this result is supported by Moussa (2015) and Rizqi and Faisal (2017). Yousuf and Felföldi (2018) found that bank capital adequacy ratio in Syria affects profitability negatively as expressed by ROE they found that stricter capital requirements means better insurance for depositors, however, this leads to a decrease in the rate of return to shareholders.…”
Section: Regression Analysismentioning
confidence: 67%
“…);Agoraki et al (2011);Thangavelu and Findlay (2011);Alam (2012);Lee and Hsieh (2013);Manlagnit (2015);Maraghni and Rajhi (2015);Moussa (2015);Mohammed and Wetere (2016);Yousuf and Felföldi (2018).…”
mentioning
confidence: 99%
“…In addition, banks are required to have a sufficient amount of capital, both to support its business expansion as well as a buffer to prevent an to absorb any unexpected losses (Raharjo et al, 2014). Bank uses capital to finance investments and decrease the likelihood of bankruptcy (Moussa, 2015) as well as to compete in global markets (Fitrianto et al, 2006). In line with this, Bank Indonesia, through Bank Indonesia Regulation No.…”
Section: Introductionmentioning
confidence: 99%
“…Research fromAbusharbeh et al (2013) states that liquidity has a positive difference on CAR. Research byMoussa (2015) states that Size, (CAP), Loan to assets (TLA), ROE and deposit to total assets have a negative difference on CAR while ROA, Capital in credit Operation (CFC) , Operating Expenses to Total Assets (CEA) and inflation rate have no effect on CAR. Nuryati and Anggono (2014) produced research that BOPO, ROE and NIM had Several previous studies on CAR have been led byBatani et al (2014),Mouss (2018), andDreca (2013).…”
mentioning
confidence: 99%